Ballistic spin injection and detection in Fe/semiconductor/Fe junctions - P. Mavropoulos; Wunnicke, O; P.H. Dederichs (PHYSICAL REVIEW B, 2002)
We present ab initio calculations of the spin-dependent electronic transport in Fe/GaAs/Fe and Fe/ZnSe/Fe (001) junctions simulating the situation of a spin-injection experiment. We follow a ballistic Landauer-Buttiker approach for the calculation of the spin-dependent dc conductance in the linear-response regime, in the limit of zero temperature. We show that the bulk band structure of the leads and of the semiconductor, and even more the electronic structure of a clean and abrupt interface, are responsible for a current polarization and a magnetoresistance ratio of almost the ideal 100%, if the transport is ballistic. In particular, we study the significance of the transmission resonances caused by the presence of two interfaces.